2001
DOI: 10.1023/a:1010607307099
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: We have studied Cd2+-induced effects on mitochondrial respiration and swelling in various media as a function of the [Cd2+] in the presence or absence of different bivalent metal ions or ruthenium red (RR). It was confirmed by monitoring oxygen consumption by isolated rat liver mitochondria that, beginning from 5 microM, Cd2+ decreased both ADP and uncoupler-stimulated respiration and increased their basal respiration when succinate was used as respiratory substrate. At concentrations higher than 5 microM, Cd2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
20
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 58 publications
5
20
1
Order By: Relevance
“…Analogously, in the case of Cd 2+ , a swelling was observed on isolated mitochondria [18,[21][22][23][24] and, also in this case the swelling was facilitated by the presence of Ca 2+ . However, there is no agreement between the authors concerning the cyclosporine sensitivity.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Analogously, in the case of Cd 2+ , a swelling was observed on isolated mitochondria [18,[21][22][23][24] and, also in this case the swelling was facilitated by the presence of Ca 2+ . However, there is no agreement between the authors concerning the cyclosporine sensitivity.…”
Section: Discussionmentioning
confidence: 53%
“…However, there is no agreement between the authors concerning the cyclosporine sensitivity. In particular, Pourahmad et al [21] and Dorta et al [23], found cyclosporine sensitivity, while Belyaeva et al [24] and Li et al [18] do not find cyclosporine sensitivity. As a consequence, different mechanisms for Cd 2+ have been proposed; Li et al [18] proposed binding of Co 2+ to the thiol groups in ANT.…”
Section: Discussionmentioning
confidence: 97%
“…The onset of increased permeability is favored by massive Ca 2+ accumulation and the influence of an inducing agent [1,2]. With regard to the latter, several dissimilar reagents have been used to open the pore, i.e., inorganic phosphate [3], heavy metals [4][5][6], thiol selective reagents [7][8][9], oxidants, such as reactive oxygen-derived species [10][11][12], and organic hydroperoxides [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Cd 2+ , a dithiol blocking reagent, triggers mitochondrial K + uptake [17], promotes non-specific permeability [18], and inhibits Ca 2+ influx [6,19,20]. Nonspecific permeability increase to matrix solutes can also be stimulated by the monofunctional thiol reagents, mersalyl [21] and N-ethylmaleimide [22], as well as by the dithiol reagent phenylarsine oxide [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of divalent metals (and of Al 3+ , phenylarsine oxide and oxidising compounds), which are inducers of the cyclosporinesensitive swelling, the proposed molecular mechanism was that the ANT (adenine nucleotide traslocase) (where the metals and the oxidant agents form an intramolecular cross-linking between the Cys 160 and Cys 257 thiol groups) is a target site [17,24,25,[29][30][31][32][33][34][35].…”
mentioning
confidence: 99%